A Comparison between Silver Nanosquare Arrays and Silver Thin-Films as a Blood Cancer Prognosis Monitoring Electrode Design Using Optical and Electrochemical Characterization - Nasori Nasori; Ulya Farahdina; Vinda Zakiyatuz Zulfa; Miftakhul Firdhaus; Ihwanul Aziz; Darsono Darsono; Dawei Cao; Zhijie Wang; Endarko Endarko; Agus Rubiyanto (Nanomaterials, 2021)
The development of silver (Ag) thin films and the fabrication of Ag nanosquare arrays with the use of an anodic aluminum oxide (AAO) template and leaf extracts were successfully carried out using the DC sputtering and spin coating deposition methods. Ag thin films and Ag nanosquare arrays are developed to monitor cancer prognosis due to the correlation between serum albumin levels and prognostic factors, as well as the binding of serum albumin to the surface of these electrodes. Nanosquare structures were fabricated using AAO templates with varying diameters and a gap distance between adjacent unit cells of 100 nm. The nanosquare array with a diameter of 250 nm and irradiated with electromagnetic waves with a wavelength of around 800 nm possessed the greatest electric field distribution compared to the other variations of diameters and wavelengths. The results of the absorption measurement and simulation showed a greater shift in absorption peak wavelength when carried out using the Ag nanosquare array. The absorption peak wavelengths of the Ag nanosquare array in normal blood and blood with cancer lymphocytes were 700–774 nm and 800–850 nm, respectively. The electrochemical test showed that the sensitivity values of the Ag thin-film electrode deposited using DC sputtering, the Ag thin-film electrode deposited using spin coating, and the Ag nanosquare array in detecting PBS+BSA concentration in the cyclic voltammetry (CV) experiment were 1.308 µA mM−1cm−2, 0.022 µA mM−1cm−2, and 39.917 µA mM−1cm−2, respectively. Meanwhile, the sensitivity values of the Ag thin film and the Ag nanosquare array in detecting the PBS+BSA concentration in the electrochemical impedance spectroscopy (EIS) measurement were 6593.76 Ohm·cm2/mM and 69,000 Ohm·cm2/mM, respectively. Thus, our analysis of the optical and electrochemical characteristics of Ag thin films and Ag nanosquare arrays showed that both can be used as an alternative biomedical technology to monitor the prognosis of blood cancer based on the concentration of serum albumin in blood.